Development Of Assessment Instruments Based On Science Literacy On Class X Environmental-Change Materials - Rahma Fitri; L Lufri; Yosi Laila Rahmi; Tut Anggraini; Niken Fryolta; Syamsurizal Syamsurizal (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2021)
Based on PISA data, it shows that the scientific literacy position of Indonesian students is still in the last 10th rank compared to other countries. This shows the lack of skills of Indonesian students in solving PISA questions because in the learning process the assessment instruments used in schools have not reached the criteria for scientific literacy competence. This study aims to produce an assessment instrument based on environmental-change science literacy in class X students that is valid, practical, has varying levels of difficulty, has good discriminatory power, and is reliable. This type of research is research and development with a 4-D development model. The research subjects consisted of 47 students of class X of SMAN 16 Batam and the validators consisted of 2 lecturers of FMIPA UNP and 1 teacher of SMAN 16 Batam. This study resulted in a logically valid scientific literacy-based assessment instrument (85.26%). The results of the practical test of scientific literacy-based assessment instruments by teachers and students respectively were an average score of 82.77% (teachers) and 82.44% (students). The results of the analysis of instrument items using ANATES Version 4.09 are: on multiple choice questions of 0.40-0.69 (medium to high correlation), and very high reliability (0.90); on the questions of description, compound, and attitude of 0.34-0.80 (low to high correlation), and very high reliability (0.81). In the test of discrimination power of questions and the level of difficulty of the questions, the scores are quite varied.